2011
DOI: 10.1002/cphc.201100589
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the B4 Liquid Crystal Phase near a Glass Surface

Abstract: The B4 liquid crystal phase of bent-core molecules, a smectic phase of helical nanofilaments, is one of the most complex hierarchical self-assemblies in soft materials. We describe the layer topology of the B4 phase of mesogens in the P-n-OPIMB homologous series near the liquid crystal/glass interface. Freeze-fracture transmission electron microscopy reveals that the twisted layer structure of the bulk is suppressed, the layers instead forming a structure with periodic layer undulations, with the topography de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
1
31
2
1
Order By: Relevance
“…Therefore, we conclude that even the first layer is made of helical filaments. This is very different from prior FFTEM studies on the n ¼ 7 homologue near a flat and rigid glass substrate that revealed focal conic domains formed under the influence of the surface forces near the substrate 17,22 . Our observations of only slightly distorted nanofilaments suggest that the carbon substrate preserves the structural features pertinent to the bulk structure of the HNF phase, despite the relatively small thickness of the samples (40-120 nm).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, we conclude that even the first layer is made of helical filaments. This is very different from prior FFTEM studies on the n ¼ 7 homologue near a flat and rigid glass substrate that revealed focal conic domains formed under the influence of the surface forces near the substrate 17,22 . Our observations of only slightly distorted nanofilaments suggest that the carbon substrate preserves the structural features pertinent to the bulk structure of the HNF phase, despite the relatively small thickness of the samples (40-120 nm).…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, Chen et al 17 have already observed that at the surfaces, where parabolic domain walls form, the HNFs axes are tilted by gB38°with respect to a periodic one-dimensional modulation. However, this rotation was not explained, and no subsequent rotations of the filaments with respect to each other was assumed 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the structures found at a glass interface from a broken planchet sample in work by Chen et al 10 Because helical nanofilaments cannot make full contact with the surface, instead of forming helical nanofilaments, P-9-OPIMB form some typical lamellar surface structure. These regions are usually large.…”
Section: ■ Methodssupporting
confidence: 86%
“…Specifically the repeating, twisted texture seen in Figure 2A has previously been identified as characteristic of the HNF phase. 1,10,25 The topology of the as-spun sample on the surface of the quartz is shown in Figure 2A. The P-9-OPIMB is dissolved in chloroform and spin-coated on the surface of the quartz.…”
Section: ■ Methodsmentioning
confidence: 99%